Response to the revised offer on the variation of facade work (Variation Order # 031) of BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding response to the revised offer on the variation of facade work (Variation Order # 031) of BRAC University new campus project.